Dracula - Stoker, Bram, 1847-1912.; Gelev, Penko; Macdonald, Fiona (Hauppage, NY : Barron's Educational Series, 2007)
This book is the classic macabre tale of the urbane vampire, Count Dracula of Transylvania, and the small group of people who vowed to rid the world of him.
Includes filmography (p. 47) and index.
Library Media Connection
School Library Journal
4.8
3-6.
3-6
Keywords: Dracula, Count (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Vampires -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Dracula, Count (Fictitious character) -- Fiction; Horror stories; Vampires -- Fiction; Comic books, strips, etc; Dracula, Count (Fictional character) -- Comic books, strips, etc -- Fiction; Horror fiction; Vampires -- Comic books, strips, etc -- Fiction; Transylvania -- Comic books, strips, etc -- Fiction; Transylvania -- Fiction; Transylvania -- Comic books, strips, etc -- Fiction; Graphic novels; Horror comic books, strips, etc